Pengembangan Media Pembelajaran Video Animasi Berbasis Animaker pada Mata Pelajaran IPS di SMP Negeri 2 Kadugede (Indo-MathEdu Intellectuals Journal, 2025)
The lack of the use of technology-based learning media, especially in Social Sciences subjects, causes students to feel bored and easily sleepy because learning feels monotonous. This research aims to develop animated video learning media based on Animaker for IPS subjects at SMP Negeri 2 Kadugede. The development model used is ADDIE, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study involved 20 eighth-grade students conducted in 2 trial cycles, namely a small group of 6 people and a large group of 14 people. Data collection techniques were carried out using validation sheets and feasibility questionnaires by users (students). The results showed that the validity of the media obtained a value of 100% in the "Very Feasible" category from material experts and 91% in the "Very Feasible" category from media experts. Beta test 1 obtained a percentage of 73% in the "Good" category and beta test 2 obtained a percentage of 91% in the "Very Good" category. It can be concluded that the development of Animaker-based animated video learning media is suitabel for use in Social Studies learning.